If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 26 = 0 Reorder the terms: 26 + 2x = 0 Solving 26 + 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-26' to each side of the equation. 26 + -26 + 2x = 0 + -26 Combine like terms: 26 + -26 = 0 0 + 2x = 0 + -26 2x = 0 + -26 Combine like terms: 0 + -26 = -26 2x = -26 Divide each side by '2'. x = -13 Simplifying x = -13
| -9+2x+4x=9 | | 5x-6x-3=-5 | | 6+4(3-2n)=-4n+14 | | 1/6=1.5x | | 8y=-3x+4 | | 5b-2=18 | | 52x^3-122x^2+66x=0 | | -2n=6-2n | | -8x+8+5x=2 | | -3x+3=2 | | 6x+4.50y=45 | | 20.4/3.4= | | 2x/9-9/3=8-3x | | 6(x-2)+5x=9x-2(4-3) | | 9x+4=64 | | -7x+2y=70 | | .66x-6+3=4x-4 | | 4.5*4.4= | | 2x^2=2048 | | 3x(5x-54)= | | -5/9*(-4) | | 17d+104=998 | | 3s+144=531 | | 5(2x-2)=6x+9 | | t-671/11=19 | | 12=336/f | | -39+7x=4x-6(x+8) | | 103-8m=31 | | 36+3h=84 | | 5x-12=2x+14 | | 9x+8y+8z=40 | | -7x(-6*0)=-15 |